2021
DOI: 10.1093/nar/gkab224
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of human minisatellite VNTRs: population-specific alleles and gene expression differences

Abstract: Variable Number Tandem Repeats (VNTRs) are tandem repeat (TR) loci that vary in copy number across a population. Using our program, VNTRseek, we analyzed human whole genome sequencing datasets from 2770 individuals in order to detect minisatellite VNTRs, i.e., those with pattern sizes ≥7 bp. We detected 35 638 VNTR loci and classified 5676 as commonly polymorphic (i.e. with non-reference alleles occurring in >5% of the population). Commonly polymorphic VNTR loci were found to be enriched in genomic regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 152 publications
0
15
0
Order By: Relevance
“…To estimate haplotype-resolved VNTR allele lengths in UK Biobank participants, we applied a two-stage approach in which we first generated a reference panel of 9,376 VNTR+SNP haplotypes by analyzing short-read whole-genome sequencing (WGS) data from the Simons Simplex Collection (SSC;Fischbach andLord 2010, An et al 2018) and subsequently imputed VNTR alleles from SSC into UKB. To generate the reference panel, we first estimated individual-level VNTR lengths (summed across the two parental alleles) from sequencing depthof-coverage in 8,936 SSC participants (including 4,688 unrelated individuals whose haplotypes formed the reference panel).…”
Section: Ascertainment and Genotyping Of 15653 Vntr Polymorphisms Gen...mentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate haplotype-resolved VNTR allele lengths in UK Biobank participants, we applied a two-stage approach in which we first generated a reference panel of 9,376 VNTR+SNP haplotypes by analyzing short-read whole-genome sequencing (WGS) data from the Simons Simplex Collection (SSC;Fischbach andLord 2010, An et al 2018) and subsequently imputed VNTR alleles from SSC into UKB. To generate the reference panel, we first estimated individual-level VNTR lengths (summed across the two parental alleles) from sequencing depthof-coverage in 8,936 SSC participants (including 4,688 unrelated individuals whose haplotypes formed the reference panel).…”
Section: Ascertainment and Genotyping Of 15653 Vntr Polymorphisms Gen...mentioning
confidence: 99%
“…Most studies to date have analyzed cohorts in which participants are both phenotyped and sequenced, measuring VNTR allele lengths either directly from spanning reads or indirectly from sequencing depth-of-coverage (Course et al 2020, Bakhtiari et al 2021, Eslami Rasekh et al 2021, Garg et al 2021, Lu et al 2021, Garg et al 2022). This approach has succeeded in identifying associations between VNTRs and the expression of nearby genes (Bakhtiari et al 2021, Eslami Rasekh et al 2021, Garg et al 2021, Lu et al 2021), but discovering associations with health and disease phenotypes (Garg et al 2022) has proven more difficult due to the challenge of amassing phenotype and VNTR-allele information in the large number of individuals typically needed for genetic studies to discover genotype-phenotype associations, and the still-larger sample sizes required to distinguish among the effects of genomically nearby variants (such as VNTRs and nearby SNPs). An approach that has driven discovery of many SNP-phenotype associations is to impute untyped alleles based on the SNP haplotypes on which they segregate (Marchini et al 2007); this approach has been extended to complex and multi-allelic copy number variations (Handsaker et al 2015; Sekar et al 2016; Boettger et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The samples in the NyuWa dataset were mostly Han Chinese, in which 2999 members were previously used for investigating small variants 42 and mobile element insertions 43 . The deeply sequenced 1KGP dataset 44 has been used to detect de novo tandem repeat expansions 45 and reference minisatellite variable number tandem repeats (VNTRs) 46 , 47 , while we included it here to study variations of reference STRs and to increase population diversity. Jointly analyzing two large cohorts enabled us to obtain a systematic view of the STR variation in diverse populations, with an emphasis on Han Chinese.…”
Section: Introductionmentioning
confidence: 99%
“…On the other aspect, it is well established that variable number tandem repeats (VNTRs) functional polymorphisms are groups of polymorphisms that could affect on expression of genes through changing the number of repeats 14 . Recently, Rasekh et al have found that about 180 different genes expression correlated with their proximal VNTRs sequences 15 . This Phenomenon clearly can be seen in both 5-HTT and MAOA.…”
Section: Introductionmentioning
confidence: 99%